O ato performático da reestruturação: dissonâncias entre o discurso e os resultados em um estudo de caso brasileiro sobre financeirização - Benatti, Glauco (2016)
This paper presents a case study on the restructuring process of a Brazilian operation of a century-old Fortune 500 American multinational manufacturer of industrial equipment. The focus of the work lies with the dissonance between discourse and the result of that process, raising the hypothesis that capital market pressure is behind such restructuring. The annual reports of this company portray the restructuring as a recurring corporate strategy, through which the company seeks to boost confidence in the capital market itself and its ability to deliver better results (or reverse bad ones) without, however, such results are achieved in fact, as this case study aims to show. This institutional literature proved to be a flagship tool company speech aimed at telling the actors of the capital market, stories about the strategies set in motion in defense of the interests of shareholders. The examination of such documents for this case study revealed that these strategies unfold in sometimes more tangible actions, sometimes more performing ones and, while restructuring proved to be more performing actions; the strategy of acquisitions / divestiments in series proved to be the most tangible ones.